APPLICATION OF INQUIRY BASED LEARNING MODEL USING STEM APPROACH TO REDUCE STUDENTS' INTRINSIC COGNITIVE LOAD - Rita Sundari; Omnia Salah Ahmed; Abdurrahman Abdurrahman; Kartini Herlina (Science Education, Institut Agama Islam Negeri Ponorogo, 2021)
This study is an experimental research using a quasi-experimental design with the type of non-equivalent control group pretest-posttest. This research aims to reduce Intrinsic Cognitive Load (ICL) through Inquiry Based Learning (IBL) model based STEM approach. This research was conducted at SMA Negeri 1 Seputih Banyak with the research subjects of class X IPA 1 students and X IPA 4. An data Intrinsic Cognitive Load obtained from essay the pretest-posttest (Task Complexity worksheet). Cognitive load test data analysis was performed using the data normality test, N-gain test and hypothesis test using the Paired Sample T-Test. The experimental class implements the Inquiry Based Learning model based audio and visual using STEM approach while the control class is nonaudio and visual. The results showed by the average value of N-Gain Intrinsic Cognitive Load (ICL) in the experimental class was 0.63 with the moderate category and the control class was 0.18 with the low category. Based on data analysis, can be concluded that there is a positive influence in the form of a decrease in the cognitive load Intrinsic Cognitive Load (ICL) in the experimental class using the Inquiry Based Learning model plus an audio and visual based STEM approach.